Improving science learning achievement and creativity through surrounding natural environment approach - Ahmadi Pribadi (Jurnal Prima Edukasia, 2018)
The research aimed to improve the learning process on science competence, improve the students’ creativity, and improve the students’ science learning achievement of grade V SD Negeri Karangreja 01, Cipari district, Cilacap regency through surrounding natural environment approach. The research was Classroom Action Research. The study was conducted in two cycles. This research was conducted in SDN Karangreja 01 Cipari, Cilacap from November to December 2014. The objects were all students of grade V consisting of 17 students. The data were collected using observation, paper and pencil tests, interviews, and documentation. The results showed the implementation of surrounding natural environment approach in science instruction could improve the students’ creativity and science learning achievement of grade V. The improvement of learning process indicated through the mean score at cycle I and II which are 13 and 14 respectively. The improvement of students’ creativity and learning achievement was indicated through the mean score of creativity test, the mean score of learning achievement on the aspects of affective, psychomotor, and cognitive at cycle I and cycle II. The improvement of creativity test score at cycle I and II were 11.56 and 13.31 respectively. The improvement of affective score at cycle I and II were 2.99 and 3.58 respectively. The improvement of psychomotor score at cycle I and II were 2.50 and 3.42 respectively. The improvement of cognitive score at cycle I and II were 75.36 and 86 respectively.